PEMIKIRAN ASY-SYÂTIBÎ TENTANG MASLAHAH MURSALAH - Imron Rosyadi (Profetika: Jurnal Studi Islam, 2013)
This paper discusses the application of maslahahmursalahmethod inestablishing an Islamic law. The writerstudies AsySyatibi’s thought that defines maslahahmursalah.He writes thatmaslahahmursalahis a new case that has not beenstated in a certain argumentation (nash) but it has benefits which are in line with (almunâsib)Islamic law. The conformity in deed to the Islamic law (tasharrufât) doesnot have to be always supported by certain argumentation (nash) that underlies andrefers to the conformity but it can be a collection of argumentations that give certainbenefits (qat’i). The new cases that contain benefits and have not had their confirmationare decided by maslahahmursalah, whether accepted or refused. The cases are relatedto muamalat not to rituals. The use of maslahahmursalahas the argumentation todecide a law is just for the need that is dharûrî and hâjî. Deciding the benefits from anaction that will be used as argumentation on maslahahmursalah can use commonsensemaximallyKey words: Asy-Syatibi, maslahahmursalah, argumentationMakalah ini membahas penerapan metode maslahah mursalah dalampenetapan suatu hukum Islam. Penulis mengkaji pemikirana sy-Syâtibî, yang mendefinisikanmaslahah mursalah adalah maslahah yang ditemukan pada kasus baruyang tidak ditunjuk oleh nash tertentu tetapi ia mengandung kemaslahatan yang sejalan(al-munâsib) dengan tindakan syara.» Kesejalanan dengan tindakan (tasharrufât)syara» dalam hal ini tidak harus didukung dengan dalil tertentu yang berdiri sendiridan menunjuk pada maslahahtersebut tetapi dapat merupakan kumpulan dalil yangmemberikan faedah yang pasti (qat»î). Masalah-masalah baru yang belum adakonfirmasinya, baik dibenarkan maupun ditolak, dan mengandung kemaslahatan yangdiputuskan dengan maslahah mursalah adalah berkaitan dengan masalah-masalahmuamalat, bukan berkaitan dengan ibadah. Penggunaan maslahah mursalah sebagaidalil penetapan hukum hanya untuk kebutuhan yang sifatnya dharûrî dan hâjî.Menentukan kemaslahatan dari suatu tindakan yang nantinya akan dijadikan dasarpertimbangan dalam dalil maslahah mursalah dapat menggunakan akal secaramaksimal.Kata Kunci: Asy-Syatibi, masalahah mursalah, dalil hukum